Violent Black Man and the Myth of Black Macho in Eugene O’Neill’s “The Dreamy Kid” - Łobodziec, Agnieszka (Respectus Philologicus, 2014)
The aim of this article is the investigation of the extent to which Eugene O’Neill, in his drama The Dreamy Kid, (re)constructs, or employs, the black macho myth, which negatively images black men as marginalized and violent. This undertaking questions O’Neill’s self-proclaimed progressive racial attitudes and stated focus on the universal nature of human existence, which he professed to express through drama. Moreover, the article challenges the mainstream view of The Dreamy Kid as progressive. Although the play focalizes the experience of a marginalized black man, which could be interpreted as the playwright’s concern with the unjust racial and class stratification of American society, O’Neill’s production, unfortunately, contains a number of pervasive stereotypes relative to black people’s alleged moral degeneracy, primitiveness, and violent behavior, which threatens the white dominated constructed order. In terms of gendered racial politics, in the article attention is given to O’Neill’s presentation of black male negotiations with the white patriarchal power structure, embodied by the police forces, and with black matriarchy, represented by O’Neill’s stereotypical character portrayal of a dominant elderly black woman. Lastly, an overall analysis is performed in light of the call for an autonomous black art, which emerged among black artists in opposition to the demeaning, unrealistic, stereotypical portrayals of black victims of oppression by white American writers.
Keywords: myth of black macho; racial stereotype; violence; black matriarchy; black art